PENGARUH PROSES PRODUKSI DAN PENGENDALIAN KUALITAS TERHADAP KUALITAS PRODUK YHA DI PT. FURUKAWA AUTOMOTIVE SYSTEM INDONESIA CIKARANG - Subagiyo; Suci Desvika (POLITEKNIK LP3I JAKARTA, 2024)
The quality of a product is one of the most important factors in the industrial world as in PT. Furukawa Automotive System Indonesia. The company always tries to maintain the quality of its products, but inreality things don't go smoothly. Every month there are still a large number of damaged products (NG) both in the production process and in quality control that are not optimal. There fore the purpose of this research is to find out how much influence the production process and quality control have on the quality of the product produced either partially or simultaneously. This study uses a quantitative approach with primary data as a source of data obtained from the results of the questionnaire. Data analysis methods in this study are validity test, reliability test, classic assumption test which consists of normality test, heteroscedasticity test, multicollinearity test, linearity test, hypothesis test and determination test. The results of this study indicate that (1) the production process variable has a positive and significant effect on the product quality of PT. Fasi, (2) the quality control variable has a positive and significant effect on the product quality of PT. Fasi, (3) the production process variables and quality control variables together have an influence and are significant on the product quality of PT. Fasi.